EVALUATION OF THE INCREASE IN THE EFFICIENCY OF COOPERATION IN THE PRODUCTION OF FRUIT AND VEGETABLE PRODUCTS - Ergashev Rakhmatulla , Khidirovich (THE INNOVATION ECONOMY, 2025)
In this article, based on the organization of a fruit and vegetable cluster cooperation system, increasing its economic efficiency, taking into account the wide use of fruit and vegetable cooperatives in the activities of agroclusters, farmers and farms, as well as integration systems, to increase the economic efficiency of fruit and vegetable cooperation Proposals and recommendations have been developed to improve and satisfy the population’s demand for fruits and vegetables.